Experimental studies on the Acute Toxicity of Bos taurus.Ursus thibetanus.Moschus extrct solution(BUM) for Herbal-acupuncture - Sang-Woon Lee; Dae-In Kang; Chan-Gil Jeong; Kwang-Ho Kim; Kyung-Sun Soh (Korean Pharmacopuncture Institute, 2002)
This experiment was carried out to study on the safety assessment of Bos turesMoschus extract solution(BUM) for Herbal-acupuncture. SD rats and ICR mice were used for acute toxicity test. the results were summerized as follows; 1. In rats and mice, LD50 value could not be measured. 2. There were no abnormal finding in acute toxicity test treated BUM for Herbal-acupuncture